Determinant Factors Of Climate-Smart Rice Cultivation Production In Pasuruan: Translog Production Function Approach - Isnurdiansyah Isnurdiansyah; Netti Tinaprilla; Anisa Dwi Utami (Jurnal Agribisnis Indonesia, 2025)
The agricultural sector is a contributor to greenhouse gas (GHG) emissions and a vulnerable victim of climate change at the same time. Climate change has affected food stability and security, including rice. It is an essential commodity to pay attention to in terms of quantity, quality, and continuity. ice cultivation practices can threaten it. Climate-smart rice cultivation (CSRC) can be a solution and needs to be introduced to respond to these challenges. CSRC is one of the programs carried out by The World Agroforestry Center (ICRAF) through The ‘Rejoso Kita Phase 2’ project in Pasuruan District to respond to existing farming practices that are unsustainable, such as excessive use of rice seeds, water for irrigation, fertilizer use, and pesticide use. This study aims to determine the production factors of CSRC using the transcendental logarithmic (Translog) production function approach. One hundred sixty-eight farmers in Pasuruan were involved in the farmer household survey collected through a structured digital questionnaire. The constructed production function model utilized nine variables. Seeds, N fertilizer, P fertilizer, K fertilizer, chemical pesticide, and chemical pesticide variables were statistically significant, with only variable of K fertilizer having a negative effect. Meanwhile, land size, organic fertilizer, and labor are not significant. The average productivity of farmers is higher than the average productivity of Pasuruan District. Combating global warming can be achieved without sacrificing yields, and it can provide a better understanding to encourage wider adoption of CSRC innovation technology. Intensive extension and mentoring related to CSRC components for farmers is an essential policy implication that needs to be implemented to maximize rice productivity and reduce negative externalities.